2011
DOI: 10.1021/nn1014215
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Electrical Reduction and Oxidation of Graphene Oxide

Abstract: Cataloged from PDF version of article.We demonstrate that graphene oxide can be reversibly reduced and oxidized using\ud electrical stimulus. Controlled reduction and oxidation in two-terminal devices containing multilayer\ud graphene oxide films are shown to result in switching between partially reduced graphene oxide and\ud graphene, a process which modifies the electronic and optical properties. High-resolution tunneling\ud current and electrostatic force imaging reveal that graphene oxide islands are forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 43 publications
4
135
0
1
Order By: Relevance
“…This enables modulating the band gap as demonstrated in its current-voltage (I-V) characteristics . Ekiz et al's study also emphasizes the importance of tuning the degree of both oxidation and reduction between gradual decrease and increase of the amount of oxygen in rGO (Ekiz et al, 2011).…”
Section: Selected Techniques For Rgo Production and Exfoliation Procementioning
confidence: 98%
“…This enables modulating the band gap as demonstrated in its current-voltage (I-V) characteristics . Ekiz et al's study also emphasizes the importance of tuning the degree of both oxidation and reduction between gradual decrease and increase of the amount of oxygen in rGO (Ekiz et al, 2011).…”
Section: Selected Techniques For Rgo Production and Exfoliation Procementioning
confidence: 98%
“…It is found that the reversible behavior could repeat for >100 cycles (about 1 h), as shown in Fig. S1, which is much more than that in multilayer GO with just several cycles [25]. Moreover, the modulated depths of transmission light in mGO are significantly improved compared with that in graphene of about 1.5% [29].…”
Section: Resultsmentioning
confidence: 87%
“…This explains the origin of non-zero current at 0V, when the device is swept from -4 to +4V. Ekiz et al [36] reported the formation of RGO from the GO by electrical bias. When the negative voltage is applied, the electrochemical reaction takes place, resulting in the reduction of GO.…”
Section: Resultsmentioning
confidence: 95%